Las relaciones culturales entre España y Estados Unidos, de la Guerra Mundial a los Pactos de 1953 - Delgado Gómez-escalonilla, Lorenzo (Cuadernos de Historia Contemporánea, 2003)
Civil War provoked a hard breaking in Spain-United States relations. Both countries became rivals in Latin America during World War II, though after their entry into war, the United States established a propaganda apparatus in Spain, with informative and cultural purposes, which continued working long after the conflict was over. Nevertheless, the political nature of Franco’s regime prevented Spain from being inserted into the cultural, educative and scientific interchange circuits created by the United States during the postwar era. The insertion did not take place unit the development of Cold War increased the value of Spain’s strategic position, pushing into the background former ideological prejudices against Franco’s regime.The bilateral pact of 1953 were immediately preceeded by cultural agreements, in order to make easier for the United States to fulfill their objectives in Spain, by preparing selected sectors of Spanish society.